2013
DOI: 10.1093/pcp/pct139
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Pyrophosphatase/Phosphodiesterase 1 Exerts a Negative Effect on Starch Accumulation and Growth in Rice Seedlings under High Temperature and CO2 Concentration Conditions

Abstract: Nucleotide pyrophosphatase/phosphodiesterase (NPP) is a widely distributed enzymatic activity occurring in both plants and mammals that catalyzes the hydrolytic breakdown of the pyrophosphate and phosphodiester bonds of a number of nucleotides. Unlike mammalian NPPs, the physiological function of plant NPPs remains largely unknown. Using a complete rice NPP1-encoding cDNA as a probe, in this work we have screened a rice shoot cDNA library and obtained complete cDNAs corresponding to six NPP genes (NPP1–NPP6). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 77 publications
0
26
0
Order By: Relevance
“…Recent investigations have revealed the dual targeting of proteins to Golgi apparatus and plastids in Arabidopsis (Villarejo et al ., ), rice (Asatsuma et al ., ; Chen et al ., ; Kaneko et al ., , ; Kitajima et al ., ; Nanjo et al ., ) and photosynthetic micro‐organisms (van Dooren et al ., ; Nowack and Grossman, ; Sláviková et al ., ). To test the possibility of plastid‐targeting of MSD1, we cobombarded MSD1‐YFP with a sequence encoding a plastid marker, the transit peptide of Waxy (Klösgen and Weil, ) fused to red fluorescent protein from Discosoma sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent investigations have revealed the dual targeting of proteins to Golgi apparatus and plastids in Arabidopsis (Villarejo et al ., ), rice (Asatsuma et al ., ; Chen et al ., ; Kaneko et al ., , ; Kitajima et al ., ; Nanjo et al ., ) and photosynthetic micro‐organisms (van Dooren et al ., ; Nowack and Grossman, ; Sláviková et al ., ). To test the possibility of plastid‐targeting of MSD1, we cobombarded MSD1‐YFP with a sequence encoding a plastid marker, the transit peptide of Waxy (Klösgen and Weil, ) fused to red fluorescent protein from Discosoma sp.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the dominant‐negative and constitutive‐active mutants of ARF1 and SAR1 GTPases arrested the plastid‐targeting of MSD1‐YFP (Figure d), and the MSD1‐YFP fluorescence was rearranged into an ER tubular network (Figure b). This indicates that MSD1 is transported from the Golgi apparatus via the secretory pathway to the plastid, as are Arabidopsis CAH1 (Burén et al ., ; Villarejo et al ., ), O. sativa AmyI‐1 (Asatsuma et al ., ; Kitajima et al ., ) and NPP1 (Kaneko et al ., , ; Nanjo et al ., ). This is the first report of the Golgi‐to‐plastid traffic of noncarbohydrate metabolism‐related enzyme.…”
Section: Discussionmentioning
confidence: 97%
“…Each enzyme plays a distinct role, but presumably functions as part of a network [21,65,66]. The NPPs are also important because they catalyse the hydrolytic UDP-glucose to produce precursors for the synthesis of starch [41]. Two AGPase genes, two NPPS genes, two SS genes, one GBSS and two SBE genes were highly expressed during germination.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleotide pyrophosphatase/phosphodiesterases (NPPs, EC 3.6.1.9) are widely distributed N-glycosylated enzymes that catalyze the hydrolytic breakdown of the pyrophosphate and phosphodiester bonds of numerous nucleotides and nucleotide sugars, and previous studies have suggested that NPP1 exhibits the highest hydrolyzing activity towards ADP-glucose, ADP-ribose, ATP and UDP-glucose [38][39][40][41]. In our results, three NPPS-encoding genes (Che006880, Che018517, and Che032493) were differently expressed during seed germination, and two genes (Che006880 and Che032493) were expressed at higher levels in T01.…”
Section: Identification Of Genes Critical For Starch and Sucrose Metamentioning
confidence: 99%
“…The situation is complicated by the lack of sequence determination and an overlap of the catalyzed reaction with other enzyme families, i.e., purple acid phosphatases (PAP; Li et al, 2002 ; Olczak et al, 2003 ) and Nudix hydrolases ( nu cleoside di phosphate compounds linked to a moiety, X; Maruta et al, 2012 ), which catalyze hydrolytic breakdown of pyrophosphate and phosphodiester bonds of numerous nucleotide sugars. Chloroplast localized ADP-Glc pyrophosphatase that belongs to purple acid phosphatase family has been found to negatively regulate starch biosynthesis in rice and barley ( Nanjo et al, 2006 ; Kaneko et al, 2014 ). The only plant enzyme characterized to date resembling the mammalian ones has been found in wheat ( Joye et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%